2015
DOI: 10.1021/nn506107c
|View full text |Cite
|
Sign up to set email alerts
|

UV-Emitting Upconversion-Based TiO2 Photosensitizing Nanoplatform: Near-Infrared Light Mediated in Vivo Photodynamic Therapy via Mitochondria-Involved Apoptosis Pathway

Abstract: Photodynamic therapy (PDT) is a promising antitumor treatment that is based on the photosensitizers that inhibit cancer cells by yielding reactive oxygen species (ROS) after irradiation of light with specific wavelengths. As a potential photosensitizer, titanium dioxide (TiO2) exhibits minimal dark cytotoxicity and excellent ultraviolet (UV) light triggered cytotoxicity, but is challenged by the limited tissue penetration of UV light. Herein, a novel near-infrared (NIR) light activated photosensitizer for PDT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
337
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 511 publications
(350 citation statements)
references
References 90 publications
4
337
0
1
Order By: Relevance
“…[32][33][34][35][36][37][38] Therefore, UCNPs have been recently used as building blocks in the construction of multimodal contrast agents for imagingguided therapy. [39][40][41][42][43][44][45] In the current study, upconversion nanoparticles (UCNPs) were first prepared by a typical solvothermal method. A polyaniline photothermal therapeutic shell was then formed by the polymerization of an aniline monomer in acid aqueous conditions, thereby obtaining polyaniline-coated UCNPs (UCNPs-PANPs).…”
Section: Xing Et Almentioning
confidence: 99%
“…[32][33][34][35][36][37][38] Therefore, UCNPs have been recently used as building blocks in the construction of multimodal contrast agents for imagingguided therapy. [39][40][41][42][43][44][45] In the current study, upconversion nanoparticles (UCNPs) were first prepared by a typical solvothermal method. A polyaniline photothermal therapeutic shell was then formed by the polymerization of an aniline monomer in acid aqueous conditions, thereby obtaining polyaniline-coated UCNPs (UCNPs-PANPs).…”
Section: Xing Et Almentioning
confidence: 99%
“…The antiapoptotic protein Bcl-2 can counteract the proapoptotic activity from Bax, and the ratio of Bax/Bcl-2 might be another useful factor in the cellular threshold for undergoing apoptosis induced by PDT. 45 Many studies have shown that activation of the caspase protein family triggers the apoptotic process in cells. Caspase-9 cleaved and activated procaspase-3.…”
mentioning
confidence: 99%
“…The reduced ratio of red to green fluorescence intensity can be calculated as ∆Ψ m , which indicates mitochondrial depolarization. 62,63 As shown in Figure 5A and B, the ∆Ψ m of the blank RGD-KLA-Liptreated group was 99.08%±1.67% of control (culture medium only), indicating that the blank RGD-KLA-Lips had no effect on the mitochondria. After treatment with Taxol, RGD/PTXLips, KLA/PTX-Lips or RGD-KLA/PTX-Lips for 10 h, the ∆Ψ m was 67.99%±6.78%, 73.65%±1.92%, 39.91%±0.40% and 19.73%±1.27% of control, respectively.…”
Section: Mitochondria-mediated Apoptosis Pathwaymentioning
confidence: 91%